Prescribed Fire as a Tool for Controlling Tick Populations in the Southeastern United States - Jennifer M. Fill; Hope M. Miller; Raelene Crandall (EDIS, 2023)
There is an increase in reported tick-borne illnesses as the tick geographic range expands past historical boundaries. Prescribed fires, ignited intentionally for specific management goals, can indirectly affect tick abundance by disrupting tick predator and prey interactions and altering suitable tick habitat. The high temperatures during prescribed fires can also directly induce tick mortality. Repeated prescribed fires in southeastern United States tick habitat can be an affordable and environmentally conscious management option.